Mysticism of Selling Price Hamemayu Hayuning Urip Bebrayan (Kejawen Ethno-Economic Approach) - Whedy Whedy Prasetyo (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2021)
The qualitative research of this kejawen ethno-economic aims to reveal actions kejawen culture of hamemayu hayuning urip bebrayan. Culture staple seller of panunggalan community in Gede Traditional Market-Surakarta makes people together with buyers. This atmosphere makes selling price determination is not solely economic benefits as much as possible. Therefore, the cultural tradition of hamemayu hayuning urip bebrayan becomes an analytical tool. Data was collected through participant observation of the panunggalan community and scholars. The results show cultural mysticism affects selling the price-determining concept that combines economic and non-economic values. This combination makes selling activities profit and loss and a spiritual and social belief that God gives sustenance through the buyer. An achievement makes it easy for sellers to feel what the buyer feels and considers the buyer, not someone else. This inner and outer whole conviction gave rise to kejawen ethno-economic. Ethno-economics is a transaction activity based on sympathetic feelings and thoughts not to harm (rumangsa handarbeni) by prioritizing honesty and kindness between seller and buyer. The activities of economic actors originate from the balance between the way of life and activities. The balance to always remember and obey God and love fellow humans as a form of guidelines for living life. Guidelines are the essence of life serenity according to God's will. This condition fosters a close brotherhood of increasing brothers (sedulur). Fraternal relations as a form of harmonious interaction, so far, have provided fluency (pelarisan) and wealth (pesugihan)